2014
DOI: 10.1186/1471-2334-14-452
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum procalcitonin as biomarker for detection of bacterial peritonitis: a systematic review and meta-analysis

Abstract: BackgroundBacterial peritonitis is serious disease and remains a diagnostic challenge for clinicians. Many studies have highlighted the potential usefulness of procalcitonin (PCT) for identification of bacterial peritonitis, however, the overall diagnostic value of PCT remains unclear. Therefore, we performed a meta-analysis to assess the accuracy of PCT for detection of bacterial peritonitis.MethodsWe performed a systematic searched in MEDLINE, EMBASE, SCOPUS, China Biology Medicine Database (CBM), China Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…5 Recently, biomarkers such as CRP and IL-6 (interleukin 6) have been considered as an interesting tool to early diagnose postoperative complications in other surgical fields. [14][15][16] CRP seems to be a good predictor of septic complications after elective colorectal surgery, as shown in a recent prospective study on 133 patients from Ortega-Deballon et al 17 With a cutoff of 125 mg/L in 4th POD, they obtained a sensitivity of 81.8% and a NPV of 95.8%. 17 Moreover, Scepanovic published similar results on 156 patients, getting the best sensitivity and specificity in 3rd POD (73% and 73%, respectively) with a CRP cutoff of 135 mg/L.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…5 Recently, biomarkers such as CRP and IL-6 (interleukin 6) have been considered as an interesting tool to early diagnose postoperative complications in other surgical fields. [14][15][16] CRP seems to be a good predictor of septic complications after elective colorectal surgery, as shown in a recent prospective study on 133 patients from Ortega-Deballon et al 17 With a cutoff of 125 mg/L in 4th POD, they obtained a sensitivity of 81.8% and a NPV of 95.8%. 17 Moreover, Scepanovic published similar results on 156 patients, getting the best sensitivity and specificity in 3rd POD (73% and 73%, respectively) with a CRP cutoff of 135 mg/L.…”
Section: Discussionmentioning
confidence: 83%
“…8 On the contrary, both in our previous 10 and in the present study we showed that renal function did not impair PCT measurement and our results were consistent with Yang study. 15 In our population mean preoperative values of azotemia and creatinine were within the reference range, being respectively 17 and 0.9 mg/ dL. Six patients (1.2%) were affected by chronic renal failure (mean azotemia and creatinine being respectively 40 and 2.8 mg/dL), but we did not register statistically significant differences in the PCT values and incidence of AL between the chronic renal failure group and the patients with normal values of kidneys function.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Investigators have used CRP and PCT biomarkers mainly to discriminate infection from non‐infection status in cirrhosis . A recent meta‐analysis aiming at evaluating the diagnostic performance of PCT and CRP in ACLF patient found that PCT was a good diagnostic tool to rule‐in and CRP to rule‐out an infection …”
Section: Discussionmentioning
confidence: 99%
“…Regarding CRP and PCT, the former is mainly synthesized in the liver as a response to Interleukin-6 (IL-6) while the latter is produced by nearly all tissues in response to Τumor Νecrosis Factor-a (TNF-a) and other inflammatory cytokines. 28 Investigators have used CRP and PCT biomarkers mainly to discriminate infection from non-infection status in cirrhosis. 29 A recent meta-analysis aiming at evaluating the diagnostic performance of PCT and CRP in ACLF patient found that PCT was a good diagnostic tool to rule-in and CRP to rule-out an infection.…”
Section: Discussionmentioning
confidence: 99%